2008
DOI: 10.1111/j.1540-8191.2008.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Worsening of Patients' Quality of Life Six Months After Coronary Artery Bypass Surgery

Abstract: The predictive factors for quality of life worsening six months after CABG are female gender, diabetes mellitus, low ejection fraction, and the presence of postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…In support of these findings, we previously reported that adverse events after heart transplantation are related to HRQOL both early 36 and later 37 after heart transplantation. Similarly, post-operative complications were related to HRQOL early 38, 39 and later 40 after myocardial revascularization. Lastly, the relationship between the pre implant VAS score and change in the VAS score after implant has also been demonstrated in the cardiac surgical literature.…”
Section: Discussionmentioning
confidence: 94%
“…In support of these findings, we previously reported that adverse events after heart transplantation are related to HRQOL both early 36 and later 37 after heart transplantation. Similarly, post-operative complications were related to HRQOL early 38, 39 and later 40 after myocardial revascularization. Lastly, the relationship between the pre implant VAS score and change in the VAS score after implant has also been demonstrated in the cardiac surgical literature.…”
Section: Discussionmentioning
confidence: 94%
“…10) We have already reported on QOL improvement that patients have 6 months after CABG. 11) This prosperity is also maintained 2 years after CABG, with the fact that in the section of PM there is an additional improvement in QOL. In the first 6 months after surgery, patients are, in spite of significant repair of PM, compared to the preoperative period, spared of major physical effort.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies, however, show that diabetes is a predictor of QOL worsening after CABG. 11,20) Although the influence of diabetes to the appearance of neuropathy can be the cause of minor sensibility for each pain, even for angina although in this case is more important diabetes impact on the progression of coronary artery disease and the re-emergence of anginal pain. In addition, in diabetics with coronary disease, in comparison to non-diabetics, depression after serious cardiovascular events is more frequent.…”
Section: Discussionmentioning
confidence: 99%
“…This was also found in studies with CABG patients [25], [26], [27], [28], [29], [30] or patients with coronary artery disease [31]. Furthermore, obesity and diabetes mellitus were previously found to be predictors of health status [26], [27], [28], [30], [32]. However, this was not found in studies that measured health status post-PCI.…”
Section: Discussionmentioning
confidence: 71%
“…Regarding CABG patients, several studies determined predictors of health status [25], [26], [27], [28], [29], [30], [32], [38], [39], [40], [41], [42]. Some studies had a follow-up duration of several years [25], [26], [27], [28], [41].…”
Section: Discussionmentioning
confidence: 99%